Private Takings of Land for Urban Redevelopment: A Tale of Two Cities. (8th November 2021) - Low, Kelvin F K; Wan, Wai Yee; Chan, Alwin
Abstract: In 1999, both Hong Kong and Singapore brought into force legislation that permitted a supermajority of apartment owners within a building development that met certain statutory criteria to force a minority of dissenters to sell the development as a whole. Both territories did so because, as land-scarce cities, it was considered that the redevelopment of aging buildings was an urgent imperative. In so doing, although they claimed to be following other jurisdictions, both Hong Kong and Singapore broke new ground in pioneering the private takings of land among common law jurisdictions. These developments have proven controversial in both territories, although the controversies have differed because of differences in implementation and historical background in both cities, despite their shared past as British colonies in Asia. This Article compares the two regimes to each other as well as to a more mature regime permitting private takings of shares in mergers and acquisitions law to highlight the lessons to be learned in order to prevent abuse.